PENGARUH KESELAMATAN KERJA DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PADA SEKTOR PEMBANGKITAN MALUKU PLTD KAYU MERAH PT. PLN (PERSERO) CABANG TERNATE - Muhammad Asril Arilaha1 (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2018)
Purpose of this study was to determine the effect of partial and simultaneous variables of the Occupational Safety and Health on Productivity Employee in Maluku diesel Power Sector Redwoods PT. PLN (Persero) branch Ternate. Model analysis used to test the hypothesis is Multiple Linier Regression and SPSS statistical test as a tool. The study found that: (1) Safety positive and significant impact on Employee Productivity, (2) Occupational Health positive and significant impact on Employee Productivity, (3) Occupational Safety and Health jointly positive and significant impact on productivity Employee.